2019
DOI: 10.1111/cas.13953
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase ubiquitin‐specific protease 9X regulates the stability and function of E3 ubiquitin ligase ring finger protein 115 in breast cancer cells

Abstract: The E3 ubiquitin ligase ring finger protein 115 ( RNF 115) is overexpressed in more than half of human breast tumors and is implicated in the pathogenesis and progression of breast cancer. However, the mechanism behind RNF 115 overexpression in breast tumors remains largely unknown. Here we report that ubiquitin‐specific protease 9X ( USP 9X), a substrate‐specific deubiquitinating enzyme, stabilizes RNF 115 and thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
(157 reference statements)
0
15
0
Order By: Relevance
“…Ubiquitin specific peptidase 9 X-linked (Usp9x) is a prominently known for acting as the DUB to protect SMURF1 and RNF115 from proteolysis [ 71 , 72 ], and there is emerging evidence that Usp9x can also interact with other AR-containing proteins to regulate intracellular events. For instance, Usp9x has been observed to interact with the cytoskeletal protein ankyrin-3 (ANK3) to promote spine morphogenesis [ 38 , 73 ].…”
Section: Ankyrin Repeats and The Usp—working Together To Regulate mentioning
confidence: 99%
“…Ubiquitin specific peptidase 9 X-linked (Usp9x) is a prominently known for acting as the DUB to protect SMURF1 and RNF115 from proteolysis [ 71 , 72 ], and there is emerging evidence that Usp9x can also interact with other AR-containing proteins to regulate intracellular events. For instance, Usp9x has been observed to interact with the cytoskeletal protein ankyrin-3 (ANK3) to promote spine morphogenesis [ 38 , 73 ].…”
Section: Ankyrin Repeats and The Usp—working Together To Regulate mentioning
confidence: 99%
“… 34 , 35 In order to detect whether the protein degradation of RUNX2 was mediated by proteasome, proteasome inhibitors MG-132 was used in this study. 36 It was found that MG-132 could effectively increase the expression of RUNX2 protein, in addition, the protein level of RUNX2 in the absence of MAPK14 protein could be recovered to some extent. It has been reported that MAPK14 could also be degraded by ubiquitination, 37 but this phenomenon was not found in our study.…”
Section: Discussionmentioning
confidence: 96%
“…In vivo ubiquitination assay was performed as described previously . Briefly, HEK293T cells were seeded into 10‐cm dish overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting analysis, immunoprecipitation assays, and immunofluorescent staining were performed as described previously in details. [39][40][41]…”
Section: Antibodies Immunoblotting Immunoprecipitation Assays Anmentioning
confidence: 99%